Severity of COVID-19 in Pregnant Women: A Review on the Potential Role of Regulatory T Cells - Saghafi, Nafiseh; Mahmoudi, Mahmoud; Momtazi-Borojeni, Amir A.; Mirzaeian, Sara; Tavasolian, Fataneh; Sathyapalan, Thozhukat; Abdollahi, Elham; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2024)
As a physiological condition, pregnancy may cause temporary alterations in the hematological, cardiopulmonary, and immune responses, affecting the maternal susceptibility to viral infections. Pregnant women are vulnerable to infection with the influenza A virus, hepatitis E virus, MERS CoV, and SARS CoV. The agent of Coronavirus disease (COVID-19) is the SARS coronavirus (SARS CoV-2), which affects the cells upon binding to the angiotensin-converting enzyme-2 (ACE2). However, ACE2 expression is elevated in the placental tissue. However, surprisingly, COVID-19 infection in pregnant women tends to have a lower severity and mortality. Therefore, it is interesting to find the immunological mechanisms related to the severity of COVID-19 in pregnancy. Regulatory T cells (Tregs) are a subset of CD4+T cells that may play a central role in maintaining maternal tolerance by regulating immune responses. Pregnancy-induced Tregs are developed to control immune responses against paternal antigens expressed by the semi-allograft fetus. The role of uncontrolled immune responses in COVID-19 pathogenesis has already been identified. This review provides insight into whether pregnancy- induced regulatory T-cell functions could influence the severity of COVID-19 infection during pregnancy.
Keywords: Tregs